P09.07 Prevalence of mycoplasma genitalium in patients visiting hiv counselling institutions in north-rhine-westphalia, germany (sti-hit study). (13th September 2015) - Lallemand, A; Bremer, V; Jansen, K; Nielsen, S; Münstermann, D; Lucht, A; Tiemann, C
Abstract : Introduction: Patients asking for a free anonymous HIV test may have other STI such as Mycoplasma genitalium (Mg), yet Mg prevalence in that population is unknown. Among other STI, we measured Mg prevalence in patients seeking HIV testing at local public health authorities (LPHA) to inform decision making regarding Mg screening in HIV counselling institutions. Methods: LPHA in North Rhine-Westphalia screened patients for Mg infection on the basis of self-collected vaginal swabs and urine samples (men) which were analysed by transcription-mediated amplification assays (APTIMA® Mycoplasma genitalium ). LPHA staff collected information on socio-demographic characteristics, sexual and HIV testing behaviours, previous STI history and clinical symptoms. We assessed overall and group-specific Mg prevalences and their 95% confidence intervals (CI). Using binomial regression, we calculated prevalence ratios adjusted for age and level of education. Results: Eighteen LPHA collected 3204 samples, of which seventeen could not be analysed. Of the remaining 3187 samples, LPHA recruited 1751 men, 1430 women and 6 transgenders. The median age was 30 years [25–38]. Overall prevalence of Mg was 3.42% (109/3187; 95% CI: 2.8–4.1%), 72.5% of those who tested positive were asymptomatic. Mg prevalence was 1.4% (16/1174; 95% CI: 0.8–2.2%) in heterosexual men, 2.0% (11/549; 95% CI: 1.0–3.6%) in MSM, 13.6% (39/286; 95% CI: 9.9–18.2%) in female sex workers (FSW) and 3.6% (41/1144; 95% CI: 2.6–4.8%) in other women. After adjusting for age and level of education, Mg infection was 7.4 times [95% CI: 4.0–13] and 2.8 times [95% CI: 1.5–5.0] more prevalent in FSW and in other women, respectively, as compared to heterosexual men. Conclusion: The prevalence of Mg was higher in women, especially among FSW. Use of vaginal swabs in women as compared to urine samples in men may have provided more sensitive detection of Mg among women. Increased attention should be paid to Mg screening in patients seeking HIV testing at LPHA, particularly among FSW. Disclosure of interest statement: Diagnostic tests were funded by Hologic ® .